EMOTIONAL VARIABLES ON DIABETES CONTROL: INTERVENTION STRATEGIES - Méndez Carrillo, Francisco Xavier; Beléndez Vázquez, Marina (Anales de Psicología / Annals of Psychology)
In this review the effects of emotional stress on diabetic control and related interventions are examined. Findings from laboratory and field studies suggest two pathways by which psychological stress can affect the control of diabetes: directly, through the release of stress hormones and indirectly, by disrupting self-care behaviors. These results have encoureged the use of several behavioral strategies, such as relaxation or social skills training, to help diabetic patients learn to cope with stress.